Experimental investigation of flexural behaviours of hybrid engineered cementitious composite beams under static and fatigue loading - Zhu, Shiyao; Zhang, Y.X.; Lee, C.K. (Engineering structures, 2022)
[Display omitted] •Flexural behaviours of hybrid ECC beams under static and fatigue loadings studied.•Effects of three different polyethylene and steel fibre contents studied.•A four-stage multiple-cracking behaviour was observed under static loading.•Beams with 1.25% polyethylene and 0.75% steel fibre showed best performances. Due to its superior flexural performance in both static and fatigue loading, hybrid engineered cementitious composites (ECC) has a high potential for application in structural components subject to repeated loads such as highway bridge link slabs. For such applications, properties of ECC in terms of flexural strength, ductility, cracking behaviour, and especially the fatigue life are key parameters that affect its performance. In this study, four-point bending tests were conducted on 36 hybrid ECC beams subject to static and fatigue loadings. In order to investigate the effects of different fibres contents, three types of hybrid ECCs with different polyethylene fibre (PE) and steel fibre (ST) volume fractions were tested. The experimental work was designed to study the flexural strength, ductility, fatigue life as well as the cracking behaviours of the beams. It is found that by using hybrid fibre, both the static and fatigue performances of ECC could be enhanced when compared with mono-fibre ECC with similar fibre content. Test results also indicated, among the three hybrid ECCs tested, the ECC with 1.25%+0.75% PE-ST fibre showed a balanced performance on ductility, flexural strength, cracking control performance and fatigue life.